Diversity and Characterization of Endophytic Fungi Isolated From the Tropical Mangrove Species, Rhizophora mucronata, and Identification of Potential Antagonists Against the Soil-Borne Fungus, Fusarium solani - Hamzah, Tuan Noraida Tuan; Lee, Shiou Yih; Hidayat, Asep; Terhem, Razak; Faridah-Hanum, Ibrahim; Mohamed, Rozi (Frontiers in Microbiology, 2018)
Rhizophora mucronata is an important ecosystem entity of the Malaysian mangrove forest. Since the species grows in a harsh environment, any organism that is isolated from this species would be of huge interest due to its potential in having novel bioactive compounds. In the present work, we isolated, identified and characterized, a total of 78 fungal isolates harboring inside the leaf tissues of R. mucronata. Molecular identification using the nuclear ribosomal DNA internal transcribe spacer (ITS) sequences returned with high similarity matches to known sequences in the GenBank. Maximum likelihood analysis revealed the phylogenetic relationship of all isolates from this study. Most of the dominating fungal endophytes were from the genera Pestalotiopsis, followed by Alternaria and Cladosporium. Six isolates representing the genera Alternaria, Fusarium, Nigrospora, Pestalotiopsis, Phoma, and Xylaria, were further screened for their antagonism activities. Dual culture test assay revealed their inhibition percentages against the phytopathogenic fungus Fusarium solani between 45-66%, and 0.8-23% when using non-volatile test assay. Of the six isolates, only Fusarium lateritium and Xylaria sp. showed antibacterial activities against the pathogenic bacteria, Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus, with the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) ranging from 0.5 to 2 mg/mL. The DPPH radical scavenging assay recorded a high level of antioxidant activity in Xylaria sp., 3-fold above that of F. lateritium. We demonstrate for the first time, two members belonging to the endophytic fungal community in the tropical mangrove species that have potential use as antagonists and antibacterial agents for future biotechnological applications.